Examining community mental health providers' delivery of structured weight loss intervention to youth with serious emotional disturbance: An application of the theory of planned behaviour - Thomas L. Wykes; Andrea S. Worth; Kathryn A. Richardson; Tonja Woods; Morgan Longstreth; Christine L. McKibbin (Wiley, 2022)
Abstract Background Rates of overweight and obesity are disproportionately high among youth with serious emotional disturbance (SED). Little is known about community mental health providers' delivery of weight loss interventions to this vulnerable population. Objective This study examined attitudinal predictors of their providers' intentions to deliver weight loss interventions to youth with SED using the theory of planned behaviour. Design This study used a cross‐sectional, single‐time‐point design to examine the relationship of the theory of planned behaviour constructs with behavioural intention. Setting and Participants Community mental health providers (n = 101) serving youth with SED in the United States completed online clinical practice and theory of planned behaviour surveys. Main Variables Studied We examined the relationship of direct attitude constructs (i.e., attitude towards the behaviour, social norms and perceived behavioural control), role beliefs and moral norms with behavioural intention. Analyses included a confirmatory factor analysis and two‐step linear regression. Results The structure of the model and the reliability of the questionnaire were supported. Direct attitude constructs, role beliefs and moral norms predicted behavioural intention to deliver weight loss interventions. Discussion While there is debate about the usefulness of the theory of planned behaviour, our results showed that traditional and newer attitudinal constructs appear to influence provider intentions to deliver weight loss interventions to youth with SED. Findings suggest preliminary strategies to increase provider intentions. Public Contribution This study was designed and the results were interpreted as part of a larger, community‐based participatory research effort that included input from youth, families, providers, administrators and researchers. Collaborative discussions with community mental health providers and administrators particularly contributed to the study question asked as well as interpretation of results.